The Variation of Duck RIG-I-Mediated Innate Immune Response Induced by Different Virulence Avian Influenza Viruses - Zhai, Boyu; Liu, Lanlan; Li, Xiang; Lv, Xinru; Wu, Jinyan; Li, Jing; Lin, Shengze; Yin, Yuxiang; Lan, Jiaqi; Du, Jianan; Wu, Chenwei; Wen, Yi; et al. (Frontiers in Microbiology, 2022)
In recent years, the emerging highly pathogenic avian influenza (HPAI) A(H5N8) virus has been reported with features of widely spread, an expanding host range, and cross-species transmission, attracting wide attention. The domestic duck plays a major role in the epidemiological cycle of the HPAI H5N8 virus, but little is known concerning innate immune responses during influenza infection in duck species. In this study, we used two wild-bird-origin viruses, H5N8 and H4N6, to conduct duck infection experiments, and detect the load of the two viruses, and retinoic acid-inducible gene I (RIG-I) and interferon β (IFN-β) in the host's natural immune response. Through comparison, it is found that the expression levels of RIG-I and IFN-β are both fluctuating. The innate immunity starts rapidly within 6 hours after infection and is inhibited by the virus to varying degrees. The expression of RIG-I and IFN-β decreased on 1-2 days post-infection (dpi). The HPAI H5N8 virus has a stronger inhibitory effect on RIG-I than the low pathogenic avian influenza (LPAI) H4N6 virus and is the strongest in the lungs. After infection with HPAI H5N8 virus, 2 dpi, viral RNA replicates in large amounts in the lungs. It has been proven that RIG-I and IFN-β play an important role in the innate immune response of ducks to HPAI H5N8 virus infection, especially in the lungs. The main battlefield of RIG-I and IFN-β after infection with the LPAI H4N6 virus is in the rectum. Both viruses have been effectively controlled after 7 dpi. These results will help to understand the transmission mechanisms of avian influenza virus in wild ducks, and help effectively prevent and control avian influenza.